Predicting a Potential Link to Antidepressant Effect: Neuroprotection of Zhi-zi-chi Decoction on Glutamate-induced Cytotoxicity in PC12 Cells - Zhang, Yin; Luo, Yusha; Zhang, Dongqi; Pang, Bo; Wen, Jun; Zhou, Tingting (Frontiers in Pharmacology, 2021)
Zhi-zi-chi Decoction (ZZCD), composed of Fructus Gardeniae (Zhizi in Chinese, ZZ in brief) and Semen sojae praeparatum (Dandouchi in Chinese, DDC in brief), has been used as a drug therapy for depression for thousands of years in China. However, the antidepressant mechanism of ZZCD still remains unknown. This study was aimed at exploring antidepressant effects of ZZCD from the aspect of neuroprotection based on herb compatibility. Glutamate-treated PC12 cells and chronic unpredictable mild stress (CUMS)-induced rats were established as models of depression in vitro and in vivo respectively. Cell viability, lactate dehydrogenase (LDH), apoptosis rate, reactive oxygen species (ROS), glutathione reductase (GR) and superoxide dismutase (SOD), and the expressions of Bax, Bcl-2 and cyclic adenosine monophosphate-response element binding protein (CREB) were measured to compare neuroprotection among single herbs and the formula in vitro. Behavior tests were conducted to validate antidepressant effects of ZZCD in vivo. Results showed that the compatibility of ZZ and DDC increased cell viability and activities of GR and SOD, and decreased the levels of LDH, apoptosis cells and ROS. Besides, the expressions of Bcl-2 and CREB were up-regulated while that of Bax was down-regulated by ZZCD. Furthermore, the compatibility of ZZ and DDC reversed abnormal behaviors in CUMS-induced rats and displayed higher efficacy than any of the single herbs. This study revealed that the antidepressant effects of ZZCD were closely associated with neuroprotection and elucidated synergistic effects of the compatibility of ZZ and DDC based on it.